2016
DOI: 10.1093/femspd/ftw023
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania (Viannia) braziliensisamastigotes from patients with mucosal leishmaniasis have increased ability to disseminate and are controlled by nitric oxide at the early stage of murine infection

Abstract: Mucosal leishmaniasis (ML) caused by Leishmania (Vianna) braziliensis usually appears after the healing of the primary lesion when amastigotes disseminate from the infection site to the mucosal area. Here, we investigated murine infection with amastigotes obtained from patients with ML or localized cutaneous leishmaniasis (LCL). Amastigotes were used to infect wild type, IFN-γ KO and inducible nitric oxide synthase (iNOS) KO mice. Amastigotes from patients with LCL induced lesions that appeared earlier in IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, we demonstrated that Glucantime ® treatment changes the monocyte functional profile to a more effective proinflammatory. Although Glucantime ® is known for immunomodulatory mechanisms, it increases the in vitro and ex vivo production of NO and in vitro TNF‐α suggesting that it has an anti‐ L. braziliensis action that is important for parasite clearance . These findings showed that treatment with Glucantime ® creates a microenvironment unfavourable to parasite growth.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, we demonstrated that Glucantime ® treatment changes the monocyte functional profile to a more effective proinflammatory. Although Glucantime ® is known for immunomodulatory mechanisms, it increases the in vitro and ex vivo production of NO and in vitro TNF‐α suggesting that it has an anti‐ L. braziliensis action that is important for parasite clearance . These findings showed that treatment with Glucantime ® creates a microenvironment unfavourable to parasite growth.…”
Section: Discussionmentioning
confidence: 95%
“…braziliensis in human macrophages. Therefore, we evaluated microbicidal molecules known to be involved in Leishmania control [30,54,55] as possible targets of IL-32γ. Our data demonstrate that IL-32γ is linked with the induction of iNOS, cathelicidin and β-defensin 2 expression and consequently NO, LL-37 peptide, and β-defensin 2 release during Leishmania species infection.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules were induced by IL-32 in influenza virus [48] and MTB infection [8]. NO is a classical leishmanicidal molecule in mouse macrophages [30] but human macrophages produce low levels of NO. Nevertheless, in some reports this was enough to contribute for Leishmania killing [5658].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the parasite disseminates later in the disease process. It has been suggested that amastigotes from ML patients have a decreased ability to be internalized and grow more slowly than those from CL patients ( Gomes et al., 2016 ) and that stationary phase promastigotes from ML are more resistant to nitric oxide ( Ávila et al., 2018 ). These findings suggest that ML parasites are transmitted by vectors as promastigotes that are initially more resistant and more likely to disseminate ( Ávila et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Gomes et al, IFN-γ knockout (KO) mice were infected with amastigotes from patients with ML and CL. Interestingly, in mice infected with ML-derived amastigotes, cutaneous lesions appeared later, but a greater number of parasites were observed in the spleen ( Gomes et al., 2016 ). The same group later showed that the stationary-phase promastigotes derived from ML are more resistant to killing by nitric oxide (NO) and reactive oxygen species than are the CL-derived promastigotes.…”
Section: Discussionmentioning
confidence: 99%